Human health risk assessment from exposure to multiple sources of Hexabromocyclododecanes (HBCDs) in Taiwan - Shih-Lin Lo; Ren-Der Wang; Yi-Ju Chen; Yuan-Cheng Hsu; Yu-Syuan Luo; Gen-Shuh Wang (Sustainable Environment Research, 2023)
Abstract Hexabromocyclododecanes (HBCDs) are endocrine-disrupting and persistent organic compounds commonly used in consumer products such as styrofoam, fire-resistant curtains, construction, aquaculture products, and food containers. Humans can expose to HBCD via dermal, ingestion, and inhalation routes; however, the inhalation exposure to HBCDs is not well characterized, especially for the size-segregated particles, which could quickly deposit into the respiratory system. In this study, we systematically characterized the dermal and inhalation exposures and performed an aggregate risk assessment of HBCDs in Taiwan. Sampling sites were selected considering the traffic or industrial contribution for air (n = 2, Sanchung, and Taichung) and soil sampling (n = 19, near the industrial zones). The quantitative analysis of HBCDs in extracted samples was achieved using LC–MS/MS. Our results showed that the concentrations of total HBCDs ranged from 0.1 to 6.6 pg m−3 in the particulate matter samples and 0.63 to 187 μg kg−1 in soil samples, where γ-HBCD was the dominant species, followed by α-HBCD and β-HBCD. The total HBCDs in the finest particles (i.e., particle size below 0.49 μm) ranged from N.D. to 1.5 pg m−3. However, no consistent trend was observed for the isomer distribution of HBCDs among air samples. Furthermore, the margin of exposure was the lowest through the ingestion pathway (5152 to 22555) and the highest through the inhalation pathway (6.71 × 105 to 2.09 × 107), showing that HBCD-induced health risk can predominantly attribute to ingestion exposure. Nevertheless, the traffic and industrial contribution of inhalable HBCD deserves further studies.